President Commissioner Attributes and Climate Change Disclosure: Evidence from Indonesian Banking Companies - Susilowati, Nurdian; Mahmud, Amir; Santoso, Arif; Sari, Puji Novita; Lestari, Sari (Universitas Negeri Semarang, 2024)
In recent years, there has been an increased demand for information regarding companies’ risk management efforts and opportunities related to climate change. The lack of concrete evidence about companies’ efforts to address the impacts of climate change highlights the importance of climate change disclosure. The purpose of this study is to examine the influence of the attributes of the president commissioners (gender, age, and nationality) on climate change disclosure. Method: The study focuses on listed entities within the banking sector from 2020 to 2022 using a quantitative research methodology. The purposive sampling technique was used to gather a sample size of 129 observations. The data was analyzed using Stata 16. Findings: The results indicate that companies with female president commissioners tend to disclose less about climate change, while age and foreign nationality positively impact disclosure. These findings align with the upper-echelon theory and have significant practical implications. They underscore the need for policymakers to consider the president commissioner’s characteristics when developing strategies to promote climate change disclosure, given the growing importance of sustainability concerns. The robustness checks on the regression results consistently support these findings. Novelty: The president commissioner plays a crucial role in determining the success of climate change disclosure. Previous studies have analyzed commissioners’ educational backgrounds, while other crucial traits for supporting climate change disclosure, such as gender, age, and nationality, still lack empirical evidence. Additionally, there is still little attention given to the banking industry.